2023
DOI: 10.21272/mmi.2023.1-11
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Job Security in The Impact of Digital Leadership on Job Satisfaction and Life Satisfaction

Abstract: Digital leadership emerges as the reflection of technological innovation in business life into administration mentality. As well as possessing leadership skills, digital leaders can be defined as leaders who are talented in terms of information technologies, visionary, can think innovatively, increase the corporation’s performance and create the transformation required by the business. The literature emphasizes that digital leadership practices and digital transformation efforts can fail due to fear of being u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…However, Bello-Pintado et al (2019) have found that adopting technology overcomes productivity and performance. Recent studies have also demonstrated that digitalization positively correlates with performance (Marino-Romero et al, 2022; Prawati & Augustine, 2022; Tortorella et al, 2023) and employee satisfaction to stand out (Topcuoglu, 2023).…”
Section: Exploring the Interplay Between Digital Technology Transform...mentioning
confidence: 98%
“…However, Bello-Pintado et al (2019) have found that adopting technology overcomes productivity and performance. Recent studies have also demonstrated that digitalization positively correlates with performance (Marino-Romero et al, 2022; Prawati & Augustine, 2022; Tortorella et al, 2023) and employee satisfaction to stand out (Topcuoglu, 2023).…”
Section: Exploring the Interplay Between Digital Technology Transform...mentioning
confidence: 98%
“…Like psychological well-being, life satisfaction in the context of management has been properly investigated in recent years. Among the important studies, we can include, for example, [57][58][59], when these studies focus on the correlation of various factors of life satisfaction and, of course, professional performance.…”
Section: -2-life Satisfactionmentioning
confidence: 99%
“…One of the critical factors of these transformational processes is digital literacy, which increases the efficiency of the personnel potential of enterprises (Tatli et al, 2023;Kobis, Karyy, 2021;Kuzmenko et al, 2021). Also, it can generate digital leadership in companies, which contributes to increasing the efficiency of many technological and security processes (Topcuoglu et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%